Pengembangan Model Pembelajaran Berbasis Gaya Belajar Visual dengan Berbantuan Media Augmented Reality pada Mata Pelajaran IPA Biologi - Handayani, Baiq Sri; Lestari, Tri Ayu; Suyantri, Eni; Sukma, Izza Melati (Biosfer: Jurnal Pendidikan Biologi, 2025)
This study aims to develop a learning model that is valid and practical and suits the visual learning styles of students in biology subjects. This research is expected to improve student learning outcomes through technology that is more interactive and interesting. This research uses a development research method based on the Plomp model, which consists of four phases, namely initial investigation, design, realization, evaluation, and revision. The research subjects were grade X students at one of the schools in Mataram city.  The instruments used include expert validation questionnaires and user practicality assessments analyzed using a Likert scale of 1-4. The data obtained were then analyzed descriptively. The learning model developed includes four stages, namely screening, visualization, elaboration, and reflection abbreviated as SrVER. The results showed that based on the validity test by validators, the learning model based on visual learning styles with the help of AR obtained an average percentage of 88.2% in the valid category. Based on the teacher's response, a rate of 95% was obtained with a very feasible category, and based on student responses, a percentage of 81.78% was obtained with a very feasible category. Using the SrVER model with the help of AR media in this model makes learning more interesting and helps students understand the material better.